Real-world outcomes for tricuspid edge-to-edge repair: initial echocardiographic results from the TriClip bRIGHT study. (4th February 2022) - Donal, E; Shueler, R; Goebel, B; Lapp, H; Moellmann, H; Nickenig, G; Bekeredjian, R; Estevez, R; Atmowihardjo, I; Schmeisser, A; Kowalski, M; Trusty, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Background: Tricuspid regurgitation (TR) is a frequent disease with a graded increase in mortality as disease severity increases. The TriClip tricuspid valve repair system (TVRS) recently gained CE mark approval in March 2020 as a transcatheter treatment option for severe TR. The bRIGHT study was initiated to evaluate real-world safety and efficacy in patients treated with the TriClip TVRS and gather data to better understand these patients and this disease. Purpose: To report real-world, core lab adjudicated changes in TR severity and echocardiographic parameters from baseline through 30-day follow-up in subjects treated with tricuspid transcatheter edge-to-edge repair (TEER). Methods: bRIGHT is a prospective, multi-center, single arm post-market study evaluating the safety and effectiveness of the TriClip device in symptomatic patients with severe TR. Detailed echocardiographic assessment was performed on all available echo data for the first 175 enrolled subjects by an independent echo core lab. TR was categorized using a 5-grade scale, with the traditional "severe" grade further characterized as severe, massive and torrential. Results: At baseline, TR was "severe" in 98% (143/146) of subjects, which further stratifies to severe in 9% (13/146), massive in 63% (92/146) and torrential in 26% (38/146) of subjects using the 5-grade scale. At 30 days, TR was reduced by ≥1 grade in 81% of subjects, with 70% of subjects at moderate or less residual TR compared to only 1% at baseline (p < 0.0001, Figure 1). Vena contracta width decreased from 0.79 ± 0.56 mm at baseline to 0.41 ± 0.37 mm at 30 days. Effective regurgitant orifice (EROA) area decreased from 0.87 ± 0.57 cm2 at baseline to 0.38 ± 0.25 cm2 at 30-days. Similarly, regurgitant volume, PISA radius and jet area showed significant reductions (Table 1). RV end diastolic dimension decreased from 4.70 ± 0.85 cm at baseline to 4.22 ± 0.83 cm at 30 days. No changes were observed in right atrial volume or right ventricular function. Subjects were treated with 1.9 ± 0.7 clips on average, with less than a 1 mmHg increase in mean tricuspid valve gradient; average gradient was 1.12 ± 0.65, 1.92 ± 1.15 and 1.97 ± 1.81mm Hg at baseline, discharge and 30 days respectively. Tricuspid annular diameter was significantly higher in subjects with torrential TR at baseline compared to subjects with severe or massive TR (p < 0.001). Conclusions: Tricuspid TEER with the TriClip device showed significant reduction in TR severity in a real-world setting. Significant reduction were seen in vena contracta width, PISA radius, EROA, regurgitant volume and jet area among others. The majority of patients had massive TR at baseline. Future studies in larger cohorts are needed to investigate the relationship between the extent of TR reduction and clinical outcomes.